Sex‐Specific Impact of Aldosterone Receptor Antagonism on Ventricular Remodeling and Gene Expression after Myocardial Infarction - Kanashiro‐Takeuchi, Rosemeire M. (Blackwell Publishing Inc, 2009)
Aldosterone receptor antagonism reduces mortality and improves post‐myocardial infarction (Ml) remodeling. Because aldosterone and estrogen signaling pathways interact, we hypothesized that aldosterone blockade is sex‐specific. Therefore, we investigated the mpact of eplerenone on left ventricular (LV) remodeling and gene expression of male infarcted rats versus female infarcted rats. Ml and Sham animals were randomized to receive eplerenone (100 mg/kg/day) or placebo 3 days post‐surgery for 4 weeks and assessed by echocardiography. In the Ml placebo group, left ventricular end‐diastolic dimension (LVEDD) increased from 7.3 ± 0.4 mm to 10.2 ± 1.0 mm (p < 0.05) and ejection fraction (EF) decreased from 82.3 + 4% to 45.5 + 11% (p < 0.05) in both sexes (p= NS between groups). Eplerenone attenuated LVEDD enlargement more effectively in females (8.8 ± 0.2 mm, p < 0.05 vs. placebo) than in males (9.7 ± 0.2 mm, p= NS vs. placebo) and improved EF in females (56.7 ± 3%, p < 0.05 vs. placebo) but not in males (50.6 + 3%, p= NS vs. placebo). Transcriptomic analysis using Rat_230–2.0 microarrays (Affymetrix) revealed that in females 19% of downregu‐lated genes and 44% of upregulated genes post‐MI were restored to normal by eplerenone. In contrast, eplerenone only restored 4% of overexpressed genes in males. Together, these data suggest that aldosterone blockade reduces Ml‐induced cardiac remodeling and phenotypic alterations of gene expression preferentially in females than in males. The use of transcriptomic signatures to detect greater benefit of eplerenone in females has potential implications for personalized medicine.